PENINGKATAN EKONOMI DAN PEMBERDAYAAN PETANI DI KAMPUNG HIDUP BARU MELALUI BUDIDAYA TANAMAN HORTIKULTURA - T.P.M.D, Romualdus; Hayon, Paulus P.; Siamsa, Simon; Wati, Caecilia H. S; S.A, Apolinaris; Rizal, Abdul (....-...., 2023)
Kampung Hidup Baru is one of the villages in the Tanah Miring District, Merauke Regency, where the majority of the population makes their living as farmers. One of the agricultural commodities cultivated is horticultural crops, including chili plants. This commodity has the potential to be developed because it is supported by the availability of unused empty land and fertile soil conditions. Chili plants are a type of horticultural plant that has great business opportunities to be developed in Merauke. The large need for this commodity makes chilies a promising commodity. The high demand for chilies is due to the fact that they can be used as a spice in cooking and in the food industry. The chili plant is currently being developed by farmers in Kampung Hidup Baru even though economically it is not yet the main source of income. This is due to farmers' lack of understanding of marketing management, business management and group management which is not yet optimal. Therefore, with the Partner Village Development (PDM) activity, the implementing team will provide full participation in solving the problems faced by farmers, both aspects of cultivation, management and marketing. Implementation of activities includes counseling and technical guidance as a medium for transferring knowledge and technology to partners, which will be carried out en masse, through groups and individuals. The solution offered in implementing the service program is through non-physical and physical activities which are expected to (a) increase knowledge about the importance of innovation in business, (b) increase knowledge about group management, (c) improve marketing management, (d) improve the farmer's economy